UNIVERSITY INSTRUCTION IN INDUSTRIAL COST ACCOUNTING. - Atkins, Paul M. (The Accounting Review, 1928)
Abstract At the present time it is becoming more generally recognized than formerly that a business concern is made up of a series of interlocking activities or functions. To a considerable extent the administration of a business means the adequate and thorough control of the major functions. To facilitate this administration, various devices are set up, the purpose of which is to supply information to the executive or to aid him in putting into effect the policies which have been adopted. One of the means of control which has been receiving an increasing degree of attention in recent years is factory cost accounting. Hence one of the tasks which has confronted university schools of business is that of teaching their students something of the nature, operation and use of the system of records and accounts by means of which information concerning factory costs may be obtained. While a system of cost accounts and records may serve various ends, in most instances its primary reason for being is that it provides a very valuable means of control for the assistance of the general manager, his associates and assistants.